The Effect of Ageism and Willingness of Older Adult Care On Caring Behaviors Among New Graduate Nurses: A Descriptive, Correlational Study. - TARHAN, Merve; DOĞAN, Pınar (Journal of Nursology, 2026)
Objective: Despite the increasing ageing population, caring for older adults is not a highly preferred field of nursing in Türkiye and the world; studies examining the attitudes and behaviors of new graduate nurses towards older adult care are particularly limited. This study explored the effect of ageism and the willingness of older adult care on caring behaviors among new graduate nurses. Methods: A descriptive, correlational study was conducted on 225 new graduate nurses in four private hospitals affiliated with a university. Data were collected using a self-administered questionnaire, including a personal characteristics form, the Fraboni Scale of Ageism, the Willingness to Care for Older People Scale, and the Caring Behaviors Inventory-24. Data were analysed using descriptive tests, comparative tests, correlation analysis, and regression analysis. Results: Willingness of older adult care, discrimination, age, professional experience, receiving a course on gerontology, and living with an older adult accounted for 46.2% of the variance of caring behaviors (R=0.68; R²=0.46; F=31.226; P<.001). Conclusion: This study suggests the need for evidence-based gerontology course interventions to promote caring behaviors towards older adults and reduce age discrimination.